Project Management Evolution: From Traditional IT Implementations to AI-Driven Projects - Martins, Maicon Roberto (International Journal of Scientific Research and Management (IJSRM), 2023)
The rapid advancement of artificial intelligence (AI) has brought transformative changes to project management, necessitating a departure from traditional methodologies previously employed in IT project implementations. This paper explores the evolution of project management from conventional IT approaches to the dynamic demands of AI-driven projects. While foundational principles of project management—such as planning, risk management, and stakeholder communication—remain relevant, AI projects introduce unique challenges and require significant adaptations to existing frameworks.The study begins by delineating the characteristics and core principles of traditional IT project management. Traditional methods are characterized by their structured phases, fixed requirements, and a focus on sequential task execution. These principles have been foundational in achieving success in conventional IT projects through detailed planning, rigorous documentation, and predefined quality assurance measures.In contrast, AI projects are distinguished by their reliance on data, iterative development, and high levels of uncertainty. Unique characteristics of AI projects include the need for continuous experimentation, data-driven decision-making, and adaptability to evolving project requirements. The paper identifies key challenges in managing AI projects, such as dealing with data quality issues, ensuring model interpretability, and addressing ethical considerations.To effectively manage AI projects, project managers must adopt new strategies, including Agile and iterative methodologies that support flexibility and continuous feedback. The study emphasizes the importance of cross-functional teams, as AI projects require diverse expertise from data scientists, engineers, and domain specialists. Additionally, handling the inherent uncertainty in AI projects involves fostering a culture of innovation and adaptability.Key differences between traditional IT and AI project management are analyzed, highlighting variations in planning and scoping, risk management, stakeholder communication, and quality assurance. Traditional IT management relies on detailed upfront planning and predictable risk management, whereas AI projects necessitate adaptive planning, dynamic risk assessment, and ongoing model validation.The paper also addresses the transition to AI project management, discussing necessary skill adaptations for project managers, organizational changes to support AI initiatives, and the role of specialized tools and technologies. A hypothetical case study illustrates how traditional IT project management experience can be applied to an AI project, providing insights into practical adaptations and lessons learned.• LllLooking forward, the paper explores emerging trends in project management influenced by AI advancements and emphasizes the need for continuous learning and adaptation. The evolving role of project managers in the AI era is examined, underscoring the importance of embracing new methodologies and technologies to stay relevant.While core project management principles remain integral, the shift to AI-driven projects requires substantial modifications to traditional practices. Project managers must evolve their approaches to navigate the complexities of AI projects effectively, ensuring continued success in an increasingly technology-driven landscape.